A multicenter retrospective analysis of risk factors for poor outcomes after tibial pilon fractures. Issue 5 (28th September 2022) - Ashworth, Timothy J.; Alvarez, Paul M.; Laux, Jeffrey P.; Ganga, Sarat; Ostrum, Robert F.
Abstract : Background: Despite the high rate of complications associated with tibial pilon fractures, treatment often remains fairly algorithmic. This study highlights risk factors for poor outcomes to guide individualized treatment in an effort to minimize complications. Methods: One hundred and fifty-seven surgically treated pilon fractures in 151 patients over 6 yr were included. The following factors were studied: age, gender, presence of diabetes, smoking status, presence of an open fracture, Association for Osteosynthesis-Orthopaedic Trauma Association (AO/OTA) fracture classification, number of plates and incisions, time to external fixator placement, time to definitive treatment, and incisions used. The two primary outcomes were nonunion and infection/wound complications requiring re-operation. Univariate tests were used for each variable in isolation. Multiple regression models were used to control important covariates. Interactions between the number of incisions, patient history of smoking, the number of plates utilized, and patient history of diabetes were analyzed. Results: Male gender, open fracture, history of diabetes and increasing time to fixation were associated with infection/wound complications. Open fractures were strongly associated with the development of nonunion. The interaction model for diabetes and increasing number of plates showed that each additional plate used when treating patients with a history of diabetes was associated with 6.08 times higher odds of developing an infection, a marginally significant result ( P =0.065). Conclusions: Increased caution may be warranted when treating tibial pilon fractures in patients with certain risk factors. In patients with a history of diabetes, the additional dissection needed to place more implants may contribute to higher rates of infection. Level of Evidence: Prognostic Level III.